The complete adventures of charlie and mr willy wonka - Dahl, Roald; Blake, Quentin (Puffin London, 2016)
FANTASY & MAGICAL REALISM (CHILDREN'S / TEENAGE). Charlie and the Chocolate Factory and Charlie and the Great Glass Elevator together in a single bumper volume with phizz-whizzing new Roald Dahl branding! In Charlie and the Chocolate Factory, Mr Willy Wonka opened the gates of his amazing factory to Charlie Bucket, our hero, and four repulsive children. They are Augustus Gloop (greedy), Veruca Salt (spoiled), Violet Beauregard (gum-chewer) and Mike Teavee (TV addict). Next, in Charlie and the Great Glass Elevator, Charlie and his family find themselves orbiting the Earth with Mr Willy Wonka. Whoosh! So grab your gizzard! Hold your hats! Pay attention please. Mr Wonka wouldn't like to lose any of you at this stage of the proceedings... Ages 7+